Late presentation of vesicouterine rupture following vaginal birth after caesarean - Thapa, Baburam Dixit; Regmi, Mohan Chandra (Nepal Journal of Obstetrics and Gynaecology, 2022)
Vesicouterine rupture is one of the complications of vaginal birth after cesarean section. Late presentation of bladder along with uterine rupture is rarely reported in literature. A case of vaginal birth after cesarean got admitted on seventh postpartum day due to hematuria and urinary retention. On Per abdominal examination bladder was palpable. A large defect was noted in the dome of bladder on cystoscopy. The posterior wall and fundus of uterus was acting as posterior wall of urinary bladder on laparotomy. Total hysterectomy was done and bladder was repaired.